Mycorrhizal effects on glomalin-related soil protein and chlorophyll contents in coffee plants in the Peruvian Amazon - Solis Leyva, Reynaldo (2022)
The inoculation of vegetatively propagated coffee plants with arbuscular mycorrhizal fungi (AMF) prior to field establishment may positively influence the plant growth and physiology. This study aimed to evaluate the AMF effects on the glomalin-related soil protein and chlorophyll contents in vegetatively propagated coffee plants inoculated in a greenhouse and transplanted to an open field, in the Peruvian Amazon. The experiment consisted of eight treatments, in a 2 × 4 factorial design, being two coffee varieties (Caturra and Pache) and four AMF inocula (control, Moyobamba, El Dorado and Huallaga). The inocula were collected from organic coffee crops and named according to the province from which they were collected. The mycorrhizal colonization and chlorophyll content were statistically higher in the plants inoculated with AMF, if compared to the non-inoculated plants, while the glomalin-related soil protein content ranged from 61.6 to 69.1 mg g-1 and showed no statistically significant differences among the inocula, although the Moyobamba inoculum showed to be numerically superior. The effect of the coffee variety was not statistically significant among the variables under study.